The Implementation of Technology Approaches to Develop Learnersâ€™ Autonomy in Learning English - Meylina Muchlis (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
Autonomy in learning is about people taking more control over their learning in the classrooms, the purpose of learn languages and the ways in which they learn them. In this way, technology helps much in learning a language. This paper explores the autonomy as more than preference or strategy by the learner; it must be supported in a systematic way by the teacher and the curriculum for the learner to benefit. The characteristics of successful autonomous learner are explained followed by some examples that shown that learners have in common are that their attitudes were developed after they made their own decision for themselves that exclusively studying in the classroom environment was not enough. The paper also emphasis on technology approaches in developing learner autonomy, especially by using the computer and the internet. Newer technology, particularly the latest online systems, however, allows sound, movement, interactivity (for exercises, demonstrations, online discussion, etc), and the incorporation of genuine material for learning.Â Keywords: Learner autonomy, technology-based approaches, computer, internetCopyright Â© 2015 by Al-Ta'lim All right reserved